Efektivitas Penerapan Kebijakan Insentif Pajak Restoran Pada Masa Pandemi Covid-19 di Kabupaten Bandung (Studi Kasus Pada Badan Pendapatan Daerah Kabupaten Bandung) - Nopiandi, Rapli; Nurmalina, Rina (Indonesian Accounting Research Journal, 2024)
This study aims to determine the effectiveness of implementing restaurant tax incentive policies during the Covid-19 pandemic in Bandung Regency. In this study used qualitative research methods with a descriptive approach. Based on the analysis of effectiveness based on the indicators of the Bandung Regent Regulation and the theory of Makmur effectiveness, it is known that in terms of the accuracy of timing, accuracy of cost calculations, accuracy in measurement, accuracy in making choices, accuracy in thinking and accuracy in targeting can be said to have been effective. However, the elements of accuracy in carrying out orders and accuracy in determining goals cannot be said to be effective because it can be seen from the participation of taxpayers who submit applications that are still not optimal and there are still obstacles that cause difficulties in processing applications.